2013
DOI: 10.1590/0004-282x20130075
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with epilepsy and its association with depression and sleep quality

Abstract: OBJECTIVE: It was to evaluate the relationships between fatigue and excessive daytime sleepiness, sleep quality, depression and anxiety. METHODS: This was a cross-sectional study on 98 unselected adult patients with epilepsy (PWE) at a tertiary center. It used clinical-sociodemographic characteristics, fatigue measured by the SF-36 vitality subscale (VsSF-36) and the Epworth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 12 publications
1
36
0
1
Order By: Relevance
“…A previous study found that the severity of fatigue is higher in epilepsy patients than in healthy controls but the numbers of subjects in each group in that study were relatively small [1]. The present study included 270 epilepsy patients and 200 healthy control subjects, which is a greater number of participants than included in other studies investigating fatigue in epilepsy patients [1,16,17]. This may render the differences in fatigue observed in epilepsy patients and controls in the present study more reliable and valid.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…A previous study found that the severity of fatigue is higher in epilepsy patients than in healthy controls but the numbers of subjects in each group in that study were relatively small [1]. The present study included 270 epilepsy patients and 200 healthy control subjects, which is a greater number of participants than included in other studies investigating fatigue in epilepsy patients [1,16,17]. This may render the differences in fatigue observed in epilepsy patients and controls in the present study more reliable and valid.…”
Section: Discussionmentioning
confidence: 68%
“…Two previous studies found that sleep-related problems are crucial predictors of fatigue in epilepsy patients, but the particular aspects of the sleep-related problems differ among studies. Neves et al [16] included sleep quality and daytime sleepiness as candidate variables in their analysis and found that sleep quality, but not daytime sleepiness, was a significant predictor of fatigue in epilepsy patients. In contrast, Hamelin et al [17] found that daytime sleepiness was an important predictor of fatigue in epilepsy patients, although this study did not include sleep quality as a candidate predictor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations